New authority: Hamlet's politics with (and against) Carl Schmitt. Issue 3 (2nd July 2016) - Michelbach, Philip A.; Poe, Andrew
Abstract : Carl Schmitt's political thought has attained centrality in contemporary discussions of authority. Despite this, his complicated view of the interaction between religion and politics remains less well explored. We argue that his 1956 essay Hamlet oder Hekuba is essential to an understanding of Schmitt's thought on authority because it is precisely this nexus of religion and politics which is at stake in his Hamlet reading. Schmitt depicts Shakespeare – through Hamlet – as standing in the unique historical position to see the political problem (or catastrophe) of modernity: the separation of theology from politics. For him, Hamlet depicts the borderland 'in between' competing and transforming worlds – or what he terms 'the barbaric and the political.' Hamlet must resolve conflicts within himself between politics inspired by Protestant (indebted specifically to Martin Luther) and Roman Catholic religious beliefs. We argue that it is only by attending to the Hamlet of Wittenberg that the point of Schmitt's essay is revealed: modernity itself creates the problem of authority. Recognizing this core of Schmitt's thought allows us to theorize democratic authority.